Global, regional, and national burden and trends of stroke among youths and young adults aged 15–39 years from 1990 to 2021: findings from the Global Burden of Disease study 2021 - Yu, Qian; Tian, Yuan; Jiang, Nan; Zhao, Furong; Wang, Shuang; Sun, Miao; Liu, Zhining; Liu, Xin (Frontiers in Neurology, 2025)
BackgroundStroke is a leading cause of disability and mortality worldwide, with rising incidence rates among youths and young adults aged 15–39 years. However, comprehensive assessments of stroke burden in this age group at global, regional, and national levels are limited. This study examines trends in stroke incidence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021 using data from the Global Burden of Disease (GBD) study.MethodsData from the GBD study (1990–2021) were analyzed to assess the age-standardized incidence, mortality, and DALYs related to stroke in individuals aged 15–39 years. The relationship between stroke burden and the Socio-Demographic Index (SDI) was explored across 204 countries and 21 regions. Trends were analyzed using the estimated annual percentage change (EAPC) and average annual percentage change (AAPC).ResultsThis study reveals global, regional, and national trends in stroke burden among youths and young adults (15–39 years) from 1990 to 2021. In 2021, the global age-standardized stroke incidence was 757,234.61 cases, with 8.72 million DALYs and 122,742 stroke-related deaths. Although global incidence increased by 19.09%, age-standardized rates (ASRs) declined by 0.67% annually. DALYs and mortality rates also decreased globally. Notably, stroke burden increased in low and low-middle SDI regions. South Asia had the highest number of cases, while Oceania reported the highest mortality rate. These findings underscore regional disparities in stroke trends. Globally, metabolic risks (46.2%) and high systolic blood pressure (37.87%) are major contributors to stroke-related mortality.